Unidade de controle para injeção eletrônica common-rail Piezoelétrico para motor monocilíndrico - Vieira, Thales Fragoso (2017)
This work proposes the design and construction of a control unity for an electronic fuel injector capable of modify, in real time, the desired angle of injection and its duration in a singlecylinder internal combustion engine. Specifically developed for systems which use the Common- Rail technology and fuel injectors powered by piezoelectric principles, this unit makes use of microcontrollers together with IGBTs transistors and others electronic components to process a signal obtained through the rotation of the engine and produce a precise control signal for the fuel injector with begging and duration requested by the user during the engine’s operation. Tests with the help of a pulse generator and an oscilloscope were made and it was possible to observe the capability to control the start angle of injection and the injection’s duration.